Quantitative Analysis and Prevention Strategies of Acquaintance Injury Incidents from the Perspective of Multidimensional Modeling - Yu, Weihong; Yu, Haoli; Zhong, Yanhua (IEEE ... Information Technology and Mechatronics Engineering Conference (ITOEC ... ) (Online), 2025)
This paper explores the occurrence mechanism of acquaintance injury incidents through a multidimensional analysis framework, combining quantitative and qualitative research methods, and analyzes the intertwined effects of social, psychological, family, and legal factors. The research shows that the occurrence of acquaintance injury incidents is the result of the joint action of multiple factors, and preventive measures must comprehensively consider factors such as law enforcement, optimization of the social environment, and mental health intervention. Based on this, this paper proposes a series of targeted prevention strategies, including strengthening legal protection and enforcement, improving the social environment, optimizing family education, and providing mental health support. The research results provide theoretical support and practical suggestions for reducing acquaintance injury incidents and are of great significance for promoting the harmonious development of society.